2020
DOI: 10.3390/v12070770
|View full text |Cite
|
Sign up to set email alerts
|

The Mutation of the Genes Related to Neurovirulence in HSV-2 Produces an Attenuated Phenotype in Mice

Abstract: HSV-2 (Herpes simplex virus type 2) is a critical viral agent that mainly causes genital herpes and life-long latent infection in the dorsal root ganglia. Gene modification via CRISPR/Cas9 Clustered regularly interspaced short palindromic repeat sequences/CRISPR associated 9) was used here to construct HSV-2 mutant strains through the deletion of fragments of the RL1 (Repeat Long element 1) and/or LAT (Latency-associated Transcript) genes. The HSV-2 mutant strains LAT-HSV-2 and RL1-LAT-HSV-2 present different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Chromosomal rearrangements are typical of cancers that are associated with DNA tumor viruses have been reported in HSV-1 infections. 129,130 The region of the genome of HSV-1 that encodes MUT has not been analyzed but MUT it has been shown that MUT increases the frequency of histidine reversion mutation. 131,132 The transforming region of HSV-1 also encodes the gB, ICP-18.5, ICP-8, and DNA pol genes.…”
Section: The Role Of Dna Viruses In Human Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…Chromosomal rearrangements are typical of cancers that are associated with DNA tumor viruses have been reported in HSV-1 infections. 129,130 The region of the genome of HSV-1 that encodes MUT has not been analyzed but MUT it has been shown that MUT increases the frequency of histidine reversion mutation. 131,132 The transforming region of HSV-1 also encodes the gB, ICP-18.5, ICP-8, and DNA pol genes.…”
Section: The Role Of Dna Viruses In Human Cancermentioning
confidence: 99%
“…Chromosomal rearrangements are typical of cancers that are associated with DNA tumor viruses have been reported in HSV-1 infections. 129 , 130 …”
Section: Human Oncogenic Dna Virusesmentioning
confidence: 99%
“…Similar encouraging results were obtained regarding HSV-2; CRISPR/Cas9 system was used to produce a deletion mutation of the two strains of HSV-2, RL1 (Repeat Long element 1) and/or LAT (Latency-associated Transcript) genes. Compared to the wild type, The infected mice with the two mutated strains demonstrated a lower pathogenic phenotype during both phases of infections, acute and latent, and a more competent immune system ( Liu et al., 2020 ).…”
Section: Applications Of Crispr/cas Technology In Targeting Viral And...mentioning
confidence: 99%
“…Random indels (insertions and deletions) occur during NHEJ, leading to mutations and frameshifts in the target DNA, which lead to truncated proteins due to the premature stop codon in a different frame and prevent the translation of the active native protein. Lately, various studies have used the CRISPR/Cas9 technology to impair herpesvirus replication in vitro by targeting specific DNA sequences encoding viral proteins, such as HSV-1 [ 35 , 43 , 44 , 45 , 46 , 47 , 48 , 49 ], human alphaherpesvirus 2 (HSV-2) [ 50 , 51 , 52 ], human betaherpesvirus 5 (cytomegalovirus (CMV)) [ 35 ], human gammaherpesvirus 4 (Epstein–Barr virus (EBV) [ 35 , 53 , 54 ], and bovine alphaherpesvirus type 1 (BHV-1) [ 55 , 56 ].…”
Section: Introductionmentioning
confidence: 99%